Basic nickel carbonate nanosheet material and application thereof

The Ni2(OH)2CO3 nanosheets and graphene oxide composite materials prepared by hydrothermal synthesis in lithium-ion batteries were solved, and the effects of high capacity, excellent cycling performance and high specific surface area were achieved.

CN119797444APending Publication Date: 2025-04-11INST OF NEW MATERIALS & IND TECH WENZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411968812.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The application of existing alkaline nickel carbonate materials in the battery field is limited by their poor conductivity and large dimensional characteristics, resulting in insufficient performance in batteries.

Method used

Ni2(OH)2CO3 nanosheets were synthesized by a simple one-step hydrothermal synthesis method, and in-situ composited with graphene oxide with excellent conductivity to enhance the conductivity and specific surface area of ​​the material.

Benefits of technology

This method improves the capacity and cycle stability of lithium-ion batteries, enhances the conductivity and specific surface area of ​​the material, meets the needs of high power output, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797444A_ABST
    Figure CN119797444A_ABST
Patent Text Reader

Abstract

According to the basic nickel carbonate nanosheet material and the application thereof, Ni2 (OH) 2CO3 nanosheets are synthesized through a simple one-step hydrothermal synthesis method, and graphene is compounded in situ, so that the electrochemical performance of the basic nickel carbonate nanosheet material has high lithium storage reversibility and ultrahigh capacitance. The method provides higher capacity and better cycling stability for the lithium ion battery. Compared with the prior art, the preparation method is simple in process and low in cost, and the prepared Ni2 (OH) 2CO3 / GO composite material is excellent in cycle performance and rate capability in the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery electrode materials, and in particular to a basic nickel carbonate nanosheet material and application thereof. Background Art

[0002] Nanostructured metal oxides and semiconductor materials are highly desirable for advanced electronic, magnetic, optoelectronic and sensing applications. The performance of nanoparticles depends largely on their phase, size, shape and dimensions. Developing scalable and facile routes to produce them with controlled size and microstructure is very important for nanotechnology and synthetic chemistry. Transition metal carbonates have attracted much attention as anode materials for LIBs due to their high specific capacity. However, transition metal basic carbonates are rarely used in battery anodes and have higher theoretical specific capacity than transition metal carbonates, which is much higher than commercial carbon anode materials.

[0003] Existing nickel basic carbonate materials generally have large size characteristics, and their application scope is mainly concentrated in the field of catalysis, showing good catalytic performance. However, the poor conductivity of nickel basic carbonate has limited its application in batteries to a certain extent. Related research in the field of batteries is still insufficient, and the application potential and performance optimization of nickel basic carbonate in battery materials still need further in-depth exploration. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a basic nickel carbonate nanosheet material and application thereof.

[0005] The technical solution adopted by the present invention is as follows:

[0006] The first aspect of the present invention provides a basic nickel carbonate nanosheet material, and the preparation method thereof comprises the following steps:

[0007] S1: dispersing a soluble nickel salt in ultrapure water to obtain solution A, and dispersing a carbonate in ultrapure water to obtain solution B;

[0008] S2: adding the solution A dropwise into the solution B to mix them evenly, adding a small molecule acid to adjust the pH of the solution, and adding ultrapure water to obtain a reaction solution C;

[0009] S3: transferring solution C to a reactor for reaction;

[0010] S4: Centrifuge to obtain a solid product, wash and dry it to obtain basic nickel carbonate nanosheet material.

[0011] Preferably, in step S1, the soluble nickel salt is one or more of nickel nitrate, nickel sulfate, nickel acetate, and nickel chloride; and the carbonate is one or more of sodium carbonate and potassium carbonate.

[0012] Preferably, the molar ratio of nickel ions in solution A to carbonate ions in solution B is 1:1.0-1.3.

[0013] Preferably, in step S2, the small molecule acid is one or more of citric acid, ascorbic acid, aspartic acid, malic acid, and tartaric acid, and the pH is adjusted to 7.5-9.5.

[0014] Preferably, in step S3, the reaction time is 8-12 h and the reaction temperature is 80-130°C.

[0015] Preferably, in step S1, graphene oxide is also dispersed in solution A.

[0016] Preferably, the ratio of soluble nickel salt to graphene oxide is 13-20:1.

[0017] Preferably, the method for preparing graphene oxide comprises the following steps:

[0018] (1) adding graphite sheets and sodium nitrate into a container containing concentrated sulfuric acid placed in an ice bath and stirring;

[0019] (2) Add KMnO4 to the container and continue stirring;

[0020] (3) Transfer the container to a water bath and stir at 20-50°C;

[0021] (4) Add ultrapure water dropwise into the container to make the solution temperature below 40°C;

[0022] (5) transferring the container to a 95-100° C. oil bath and maintaining vigorous stirring for 20-40 minutes, and then continuously adding ultrapure water and H 2 O 2 at room temperature to obtain a graphene oxide solution;

[0023] (6) The GO solution is centrifuged and dialyzed until the pH value is close to neutral to obtain a concentrated graphene oxide solution, and the concentrated graphene oxide solution is vacuum dried to obtain graphene oxide.

[0024] The second aspect of the present invention provides a use of the basic nickel carbonate nanosheet material as described above in a battery.

[0025] The third aspect of the present invention provides the use of the basic nickel carbonate nanosheet material as described above in a negative electrode material for a lithium ion battery.

[0026] The beneficial effects of the present invention are as follows:

[0027] First, the present invention synthesizes Ni2(OH)2CO3 nanosheets by a simple one-step hydrothermal synthesis method, and through in-situ composite graphene, its electrochemical performance has high lithium storage reversibility and ultra-high capacitance. This method provides lithium-ion batteries with higher capacity and better cycle stability. Compared with existing reports, the preparation method of the present invention is simple in process and low in cost, and the obtained Ni2(OH)2CO3 / GO composite material has excellent cycle performance and rate performance in lithium-ion batteries.

[0028] Among them, the nanosheet-shaped Ni2(OH)2CO3 synthesized by the present invention has a very large specific surface area, which means that under the same mass or volume, the nanosheet structure can provide more active sites for the insertion and extraction of lithium ions. This high specific surface area characteristic helps to improve the electrochemical performance of the battery, especially in the process of charging and discharging, it can accelerate the transmission and reaction kinetics of lithium ions.

[0029] At the same time, the ion transmission path in the nanosheet structured Ni2(OH)2CO3 is shorter, and lithium ions can complete the embedding and extraction process in a shorter distance. This helps to improve the battery's charge and discharge rate and power performance, allowing lithium-ion batteries to complete fast charging or high-current discharge in a short period of time to meet the needs of high power output. And its unique structure helps to alleviate the volume change of the material during the charge and discharge process, reduce performance degradation, and thus extend the battery's service life.

[0030] The poor conductivity of Ni2(OH)2CO3 limits its application in batteries to a certain extent. The present invention uses a simple one-step hydrothermal method to in-situ composite it with graphene oxide material with excellent conductive properties, which improves the conductivity of the material while also refining the particle size of the material and increasing the specific surface area of ​​the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0032] Figure 1 X-ray diffraction (XRD) patterns of the three materials prepared in Examples 1-4;

[0033] Figure 2 is a transmission electron microscope (TEM) image of the basic nickel carbonate material of Example 1;

[0034] Figure 3is a transmission electron microscope (TEM) image of the basic nickel carbonate material of Example 2;

[0035] Figure 4 This is a thermogravimetric analysis diagram of the basic nickel carbonate composite graphene material of Example 2. From the diagram, it can be calculated that the graphene content of this material is about 22%.

[0036] Figure 5 The four lithium-ion batteries prepared in Examples 1-4 were subjected to 100 mA g -1 Cyclic stability test diagram at current density of ;

[0037] Figure 6 The four lithium-ion batteries prepared in Examples 1-4 were subjected to 1000 mA g -1 Cyclic stability test diagram at current density of ;

[0038] Figure 7 The four lithium-ion batteries prepared in Examples 1-4 were subjected to 2000 mA g -1 Cyclic stability test diagram at current density of ;

[0039] Figure 8 The graphs are the cycle stability test graphs of the four lithium-ion batteries prepared in Examples 1-4 at different current densities. DETAILED DESCRIPTION

[0040] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0041] Example 1

[0042] S1: In a beaker, add 3 m mol Ni(NO3)2·6H2O to 10 ml ultrapure water and mix by ultrasonic to obtain solution A. Add 3.3 m mol NaCO3 to 10 ml ultrapure water and mix by ultrasonic to obtain solution B.

[0043] S2: adding the solution B dropwise into the solution A, stirring magnetically for 20 minutes to make the mixture uniform, adding 1 mmol ascorbic acid to adjust the pH of the solution, and then adding 20 ml ultrapure water to obtain a reaction solution C;

[0044] S3: Transfer solution C to a reactor and react at 100°C for 10 h;

[0045] S4: centrifugation to obtain a solid product, washing the solid product with water and ethanol, and drying to obtain a basic nickel carbonate nanosheet negative electrode material;

[0046] S5: Weigh basic nickel carbonate negative electrode material, acetylene black and sodium alginate in a mass ratio of 7:2:1, mix evenly, add appropriate amount of ultrapure water, stir continuously into a paste, and apply it on copper foil; dry, press and assemble the copper foil coated with nano-sheet-like basic nickel carbonate negative electrode material to obtain a lithium-ion battery.

[0047] Example 2

[0048] S1: In a beaker, 3 m mol Ni(NO3)2·6H2O and 55 mg of graphene oxide were added to 10 ml of ultrapure water and mixed by ultrasonic to obtain solution A. 3.3 m mol NaCO3 was added to 10 ml of ultrapure water and mixed by ultrasonic to obtain solution B.

[0049] S2: adding the solution B dropwise into the solution A, stirring magnetically for 20 minutes to make the mixture uniform, adding 1 mmol of aspartic acid to adjust the pH of the solution, and then adding 20 ml of ultrapure water to obtain a reaction solution C;

[0050] S3: Transfer solution C to a reactor and react at 100°C for 10 h;

[0051] S4: centrifugation to obtain a solid product, the solid product is washed with water and ethanol, and dried to obtain a basic nickel carbonate nanosheet composite graphene negative electrode material;

[0052] S5: Weigh basic nickel carbonate composite graphene negative electrode material, acetylene black and sodium alginate in a mass ratio of 7:2:1, mix evenly, add appropriate amount of ultrapure water, stir continuously into a paste, and apply it on copper foil; dry, press and assemble the copper foil coated with nano-sheet-like basic nickel carbonate composite graphene negative electrode material to obtain a lithium-ion battery.

[0053] Example 3

[0054] The preparation process of this embodiment is substantially the same as that of embodiment 2, with the only difference being that in step S2, 1 mmol of aspartic acid added is replaced by 1 mmol of ascorbic acid.

[0055] Example 4

[0056] The preparation process of this embodiment is substantially the same as that of embodiment 2, with the only difference being that in step S2, 1 mmol of aspartic acid added is replaced by 1 mmol of ascorbic acid.

[0057] Material properties

[0058] Figure 1X-ray diffraction (XRD) patterns of the three materials prepared in Examples 1-4, wherein the XRD test results of the three materials are consistent with the standard card PDF#35-0501, and the peak intensity of the basic nickel carbonate composite graphene composite material is lower than that of the two basic nickel carbonate materials not composited with graphene, and it may have a smaller particle size;

[0059] Figure 2 This is a transmission electron microscope (TEM) image of the basic nickel carbonate material of Example 1, from which it can be clearly seen that it has a flaky structure.

[0060] Figure 3 This is a transmission electron microscope (TEM) image of the basic nickel carbonate material of Example 2. It can be clearly seen from the image that its flaky structure is well coated with graphene.

[0061] Figure 4 This is a thermogravimetric analysis diagram of the basic nickel carbonate composite graphene material of Example 2. From the diagram, it can be calculated that the graphene content of this material is about 22%.

[0062] Figure 5 Four lithium-ion batteries were prepared for Examples 1-4 at 100 mA g -1 Cyclic stability test diagram at current density of 100 mA g -1 After 50 cycles at a current density of -1 ; Example 2 at 100mA g -1 After 50 cycles at a current density of -1 Example 3 at 100mA g -1 After 50 cycles at a current density of -1 Example 4 at 100mA g -1 After 50 cycles at a current density of -1 ;

[0063] Figure 6 Four lithium-ion batteries were prepared for Examples 1-4 at 1000 mA g -1 Cyclic stability test diagram at current density of 1000 mA g -1 After 400 cycles at a current density of -1 Example 2 at 1000mA g -1 After 400 cycles at a current density of -1 Example 3 at 1000mA g -1 After 400 cycles at a current density of-1 ; Example 4 at 1000mA g -1 After 400 cycles at a current density of -1 ;

[0064] Figure 7 Four lithium-ion batteries were prepared for Examples 1-4 at 2000 mA g -1 Cyclic stability test diagram at current density of 2000 mA g -1 After 500 cycles at a current density of -1 Example 2 at 2000mA g -1 After 500 cycles at a current density of 1.34 W, the battery capacity is 802 mAh g -1 Example 3 at 2000mA g -1 After 500 cycles at a current density of -1 ; Example 4 at 2000mA g -1 After 500 cycles at a current density of -1 ;

[0065] Figure 8 Cyclic stability test graphs of four lithium-ion batteries at different current densities were prepared for Examples 1-4; the capacity of Example 2 was significantly higher than that of Example 1, Example 3 and Example 4 at various current densities.

[0066] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A basic nickel carbonate nanosheet material, characterized in that: The preparation method thereof comprises the following steps: S1: dispersing a soluble nickel salt in ultrapure water to obtain solution A, and dispersing a carbonate in ultrapure water to obtain solution B; S2: adding the solution A dropwise into the solution B to mix them evenly, adding a small molecule acid to adjust the pH of the solution, and adding ultrapure water to obtain a reaction solution C; S3: transferring solution C to a reactor for reaction; S4: Centrifuge to obtain a solid product, wash and dry it to obtain basic nickel carbonate nanosheet material.

2. The basic nickel carbonate nanosheet material according to claim 1, characterized in that: In step S1, the soluble nickel salt is one or more of nickel nitrate, nickel sulfate, nickel acetate, and nickel chloride; the carbonate is one or more of sodium carbonate and potassium carbonate.

3. The basic nickel carbonate nanosheet material according to claim 1, characterized in that: The molar ratio of nickel ions in solution A to carbonate ions in solution B is 1:1.0-1.

3.

4. The basic nickel carbonate nanosheet material according to claim 1, characterized in that: In step S2, the small molecule acid is one or more of citric acid, ascorbic acid, aspartic acid, malic acid, and tartaric acid, and the pH is adjusted to 7.5-9.

5.

5. The basic nickel carbonate nanosheet material according to claim 1, characterized in that: In step S3, the reaction time is 8-12 hours and the reaction temperature is 80-130°C.

6. The basic nickel carbonate nanosheet material according to claim 1, characterized in that: In step S1, graphene oxide is also dispersed in solution A.

7. The basic nickel carbonate nanosheet material according to claim 6, characterized in that: The ratio of soluble nickel salt to graphene oxide is 13-20:

1.

8. The basic nickel carbonate nanosheet material according to claim 6, characterized in that: The preparation method of graphene oxide comprises the following steps: (1) adding graphite sheets and sodium nitrate into a container containing concentrated sulfuric acid placed in an ice bath and stirring; (2) Add KMnO4 to the container and continue stirring; (3) Transfer the container to a water bath and stir at 20-50°C; (4) Add ultrapure water dropwise into the container to make the solution temperature below 40°C; (5) transferring the container to a 95-100° C. oil bath and maintaining vigorous stirring for 20-40 minutes, and then continuously adding ultrapure water and H 2 O 2 at room temperature to obtain a graphene oxide solution; (6) The GO solution is centrifuged and dialyzed until the pH value is close to neutral to obtain a concentrated graphene oxide solution, and the concentrated graphene oxide solution is vacuum dried to obtain graphene oxide.

9. Use of the basic nickel carbonate nanosheet material according to any one of claims 1 to 8 in a battery.

10. Use of the basic nickel carbonate nanosheet material according to any one of claims 1 to 8 as a negative electrode material for lithium ion batteries.